Análise espacial das Unidades Básicas de Saúde: identificando barreiras no acesso - Lopes, Elenice Jardim (2016)
Introduction: The Health Basic Unity (UBS) is one of the sites of action of the health teams in the Basic Care (AB), therefore, it needs to be placed and organized in order to make easy the population’s access to it. The National Programme of Betterment of Access and Anality of the Basic Care (PMAQ-AB) was implanted in Brazil in 2011, aiming at promoting increases in those services. Several studies point out to the barriers of access to AB, however there is shortage of researches which use special analysis. Goal: To identify barriers of access to the UBS in the municipality of São Luís, MA, Brazil. Methodology: It was performed a transversal study using secondary data and special approach in the municipality of São Luís (MA/ Brazil). The variables were divided into 3 dimensions: health service, demographical, geographical. Data about health services were collected from the collected data instrument concerning the module I of the external avaliation of the PMAQ-AB and census of the UBS in Brazil in the year of 2012. The data related to the demographical and geographical barriers were obtained from the data bank of Brazilian Geographical and Statistic Institute (IBGE) of the year 2010, of the Maranhense Institute of Socialeconomical and Geographical Studies (IMESC) of the year 2013 and of the City, Research and Urban and Rural Institute (INCID) of the year of 2013. To the descriptive analysis it was used the Stata 11. O programme and to the spacial analysis were made maps being used the ArcGis (version 11.0) system. Results: The main barriers of access to the UBS were un functioning of the UBS in the night (98%) and in the week-ends (76%), absence of environments like hospitality lounge (72%) and toilet room adapted to peoples under deficiency (84%) and no-existence of quick-tests: syphilis (94%), pregnancy (82%) and HIV (94%). In the spacial analysis were identified a bad geographical distribution due to the distant positioning of UBS in sites under high demands, proximity of other UBS’s and distant positioning of main avenues. Conclusion: There exist barriers of access to the UBS’s in the municipality of São Luís related to the offer of health services, the geographical demand and distribution.